ANALISIS TINGKAT PENDAPATAN NELAYAN KAMPUNG BIDUK-BIDUK DI KABUPATEN BERAU: ANALISIS TINGKAT PENDAPATAN NELAYAN KAMPUNG BIDUK-BIDUK DI KABUPATEN BERAU - Agus Rahmatullah (ECO-BUILD, 2018)
The purpose of research that is executed is for calculating and analyze level of income fishermen their Biduk-Biduk In Kabupaten Berau.While uses in this study is to provide an illustration on level of income their Biduk-Biduk In Kabupaten Berau and as information for the government to determine the steps will improve the income especially the fishermen in their Biduk-Biduk.Instrument the analysis used in this research is the average count. Based on the research done it was discovered that the rata-rata the fishers catch broke out at the village the same product with traditional Biduk-Biduk In Kabupaten Berau, pt pgn promised to supply the value of t to count up all ( who came after him and ) was recorded at 9,054 while t table ( tt ) was recorded at 1,691 means a sense of ownership the value of t to count up all ( ) who came after him and was greater than the value t table ( who came after him and & gt; tt ) , as a result of this hypothesis advanced by writer had been obtained by the , and what that means is the yield suggests that the income fishermen who sell their goods in the kampongs are Biduk-Biduk revenues from the divestment were built with the sweat of the needs of decent living khl is regretted by ( ) Kabupaten Berau in years 2017. There are approximately fishermen who as the principal subject should be the priority in the development of the fisheries the district area and this Berau .There are approximately fishermen who main insight into the subject of this country in its development .